2014
DOI: 10.1039/c4sm01143k
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the number of dendrimers in dendrimicelle nanoconjugates from 1 to more than 100

Abstract: The study presents a facile strategy to controllably build up dendrimicelles by self-assembly of anionic PAMAM dendrimers with cationic–neutral diblock copolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 50 publications
4
38
0
Order By: Relevance
“…This acid-terminated PAMAM dendrimers, 17 both CSC and CMC are slightly improved, and in line with other micelle systems. 14 DLS results obtained over time ( Fig.…”
Section: Nanoscale Communicationsupporting
confidence: 87%
See 2 more Smart Citations
“…This acid-terminated PAMAM dendrimers, 17 both CSC and CMC are slightly improved, and in line with other micelle systems. 14 DLS results obtained over time ( Fig.…”
Section: Nanoscale Communicationsupporting
confidence: 87%
“…This deviation from the theoretical molar charge neutrality might be attributed to the known presence of defects in higher generation PAMAM dendrimers, resulting in fewer charged end-groups and hence observed charge-stoichiometry at lower charge fraction. 17,24,25 To investigate whether or not the presence of a nanoparticle inside a dendrimer affects the formation of dendrimicelles, we mixed Au 256 DENs with block copolymer at the previously determined PMC. DLS analysis showed that dendrimicelles formed and exhibited a similar size in solution as empty dendrimicelles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides polymeric polyelectrolytes, dendrimeric structures such as poly(amidoamines) (PAMAMs) have also been used for the formation of SNPs stabilized by electrostatic interactions. Wang and co‐workers have shown that carboxylate‐terminated PAMAM dendrimers of different generations (0–9) and the cationic‐neutral diblock copolymers P2MVP 128 ‐ b ‐PEO 477 formed electrostatically stabilized micelles . Although the dendrimer size increases with generation, the resulting micellar size, structure, and number of incorporated block copolymers did not vary.…”
Section: Supramolecular Nanoparticles By Noncovalent Interactionsmentioning
confidence: 99%
“…This suggested that (dendri)micelle formation depends on the number of charges per monomeric-unit in the core and that micelle stability increases with the increase in the number of charge-per-core units. 16 A further understanding of the formation and stability of C3Ms was achieved by including nanoparticles (NP) inside dendrimers, inside micelles, with a so-called box-in-a-box structure. 17,18 In this paper, we present a new class of coacervate-core micelles (see Scheme 1), called Cyclodextrin-based Complex Coacervate Core Micelles (C4Ms), in which the cyclodextrin is covalently tethered to a dipicolinic acid (CD-DPA) unit that can coordinate to metal ions.…”
Section: Introductionmentioning
confidence: 99%